2022
DOI: 10.1186/s40001-022-00755-3
|View full text |Cite
|
Sign up to set email alerts
|

CircWDR26 regulates endometrial carcinoma progression via miR-212-3p-mediated typing genes MSH2

Abstract: Background Circular RNAs (circRNA) are important in mediating tumor progression, but their roles in endometrial carcinoma (EC) are not fully understood yet. Many circRNAs are dysregulated and may contribute to EC progression. The functions of circWDR26 in EC remain unknown. Methods The expression of circWDR26 in EC and adjacent normal tissues, and cell lines was determined by qPCR. The proliferation, apoptosis, migration, and invasion of EC cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Functionally, hsa_circ_0002577 demonstrated roles in proliferation, migration, and invasion in vitro with effects on tumor growth in vivo, attributed to the sponging of miR-197 and downstream targeting of the CTNNC1/Wnt/β-catenin axis [129]. Confirma-tion of its upregulated expression in tumor samples and in vitro and in vivo phenotypic effects, further characterization of hsa_circ_0002577 demonstrated its role in accelerating progression of EC via activation of the IGF1R/PI3K/Akt signaling pathway through sponging of miR-625-5p [130]. This circRNA, also known as circWDR26, was evaluated in EC cells and demonstrated, in addition to the previously mentioned functions, inhibition of apoptosis.…”
Section: Role Of Hsa_circ_0001610 and Hsa_circ_0002577 In Endometrial...mentioning
confidence: 86%
“…Functionally, hsa_circ_0002577 demonstrated roles in proliferation, migration, and invasion in vitro with effects on tumor growth in vivo, attributed to the sponging of miR-197 and downstream targeting of the CTNNC1/Wnt/β-catenin axis [129]. Confirma-tion of its upregulated expression in tumor samples and in vitro and in vivo phenotypic effects, further characterization of hsa_circ_0002577 demonstrated its role in accelerating progression of EC via activation of the IGF1R/PI3K/Akt signaling pathway through sponging of miR-625-5p [130]. This circRNA, also known as circWDR26, was evaluated in EC cells and demonstrated, in addition to the previously mentioned functions, inhibition of apoptosis.…”
Section: Role Of Hsa_circ_0001610 and Hsa_circ_0002577 In Endometrial...mentioning
confidence: 86%
“…It has been widely acknowledged that miRNAs are involved in circRNA's biological effects [28][29][30]. Intriguingly, CSCD database [21] analysis revealed that hsa_circ_0037858 possessed potential microRNA response elements.…”
Section: Discussionmentioning
confidence: 99%
“…Cell proliferation was assessed using the 5-ethynyl-2′-deoxyuridine (EdU) assay kit (RiboBio) according to the manufacturer’s guidelines [ 26 , 29 31 ]. Tumour cells were inoculated into 96-well plates(2 × 10 4 cells/well ) 24 h after transfection.…”
Section: Methodsmentioning
confidence: 99%